Loop mediated isothermal amplification; a review on its application and strategy in animal species authentication of meat based food products - Tasrip, Nor Asmara; Khairil Mokhtar, Nur Fadhilah; Hanapi, Ummi Kalthum; Abdul Manaf, Yanty Noorzianna; Ali, Md. Eaqub; Cheah, Yoke Kqueen; Mustafa, Shuhaimi; Mohd Desa, Mohd Nasir (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
Isothermal amplification is a technique that can amplify target DNA sequences at a single incubation temperature. Loop-mediated isothermal amplification (LAMP) is an extension of the isothermal DNA amplification technique that combines rapidity, simplicity, high specificity and sensitivity. Due to its overwhelming characteristics, LAMP has been explored for its feasibility in detecting various subjects, and recently in meat-based food products for DNA-based meat species authentication. It has been developed to target various meat species such as porcine, chicken, horse, and ostrich with sensitivity as low as 0.1 pg/μL. Further improvement with the use of magnetic beads, electrochemiluminescence and special dye such as calcein and crystal violet had increased the sensitivity of the LAMP assay. Other important characteristics were specific target gene primers as well as a shorter incubation time, warranting a good prospect for rapid testing authentication.